Formalizing Gratuitous And Contractual Transfers: A Situational Theory - Adam J. Hirsch (Washington University Law Review, 2014)
By tradition, gifts, wills, and contracts are formalized according to protocols established within each legal category. This Article examines the policies that underlie these “formalizing rules” and concludes that the utility of those rules depends fundamentally on the background conditions under which a gift, will, or contract occurs. Those background conditions, rather than the category into which the transfer falls, dictate the optimal formalizing rule for a transfer. In light of this observation, this Article proposes an integrated approach to formalizing rules that varies the required formalities for a transfer on the basis of situational criteria rather than the prevailing categorical ones.
Keywords: transfer; gift; will; contract; formalizing rules; situational criteria; tradition; integrated approach